Teacher Needs Analysis of Power Point Video to Teach Report Text in Senior High School - Fardillah, Vicky; Arrasyid, Farouk imam; Umaemah, Amroh (BABASAL English Education Journal, 2024)
This study aims to analyze the needs of teachers at various educational levels, encompassing professional, pedagogical, and welfare aspects. Professional needs include competency development through training and further education, as well as support in the use of educational technology. Pedagogical aspects involve effective teaching methods, classroom management, and relevant evaluation strategies. This study employs a qualitative method with an interview design and open-ended questionnaires to collect data. The results reveal that teachers need several points in designing research using PowerPoint videos, including the need to determine appropriate topics for writing assessments, the need for writing genres that align with the task instructions, the need to understand learning materials, the need for preparation and presentation, specific element requirements, the need to provide teaching strategies, and the need to give feedback. This research offers a new contribution to the existing literature on the use of technology in classroom learning, with a particular focus on understanding teachers' needs in learning activities through PowerPoint videos. It provides insights and best practices relevant to current and future educational situations. The study highlights the importance of preparation for teachers in online learning using PowerPoint videos and provides support to English teachers who use PowerPoint videos as a learning medium.